PENGARUH RETURN ON EQUITY, EARNING PER SHARE DAN DIVIDEN YIELD RATIO TERHADAP HARGA SAHAM LQ-45 DI BURSA EFEK INDONESIA PERIODE 2012 – 2016 - Ammanda, Rinaldi (LPPM Universitas Adiwangsa Jambi, 2018)
This research is conducted to test the effect of Return on Equity (ROE), Earning PerShare (EPS) and Dividend Yield Ratio (DYR) to Stock Price. Sampling technique usedis purposive sampling with criteria Property, Real Estate and Building constructionperiod 2012 - 2016 in Indonesia. The number of samples of 5 companies Property, RealEstate and Building construction is incorporated in the LQ45 index.From the analysis result shows that the EPS data is partially significant to the stockprice of the company Property, Real Estate and Building construction which isincorporated in LQ45 index where thitung 5,356 at level of significant less than 5%.While the ROE and DYR variables do not significantly influence the value of t -2,610and -0.346. The influence of ROE, EPS and DYR on stock price in sector property, RealEstate and Building Construction can be written with linear regression equation that isY = 858,82 - 28,92 X1 + 8,38 X2 - 32,05 X3. The amount of influence of ROE, EPSand DYR on to Stock Price in sector property, Real Estate and Building Construction is60,80% while the rest equal to 39,20% determined by other factor not specified in thisresearch.